Surgical techniques to preserve continence after robot-assisted radical prostatectomy - Katsimperis, Stamatios; Juliebø-Jones, Patrick; Ta, Anthony; Tandogdu, Zafer; Al-Bermani, Osama; Bellos, Themistoklis; Esperto, Francesco; Tonyali, Senol; Mitsogiannis, Iraklis; Skolarikos, Andreas; Varkarakis, Ioannis; Somani, Bhaskar K.; et al. (Frontiers in Surgery, 2023)
Radical prostatectomy has a significant impact on inherent anatomy of the male pelvis and the functional mechanisms of urinary continence. Incontinence has a considerable negative influence on patients' quality of life, as well as their social and psychological wellbeing. Numerous surgical techniques have been demonstrated to support the preservation of continence during robot-assisted radical prostatectomy (RARP). In this in-depth analysis, we give a general summary of the surgical techniques used in RARP and their impact on incontinence rates.